2014
DOI: 10.1109/jetcas.2014.2361068
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel FET RF Rectifier Design for Energy Harvesting Applications

Abstract: Radio-frequency (RF)-powered energy harvesting systems have offered new perspectives in various scientific and clinical applications such as health monitoring, bio-signal acquisition, and battery-less data-transceivers. In such applications, an RF rectifier with high sensitivity, high power conversion efficiency (PCE) is critical to enable the utilization of the ambient RF signal power. In this paper, we explore the high PCE advantage of the steep-slope III-V heterojunction tunnel field-effect transistor (HTFE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…In [10] we have shown that a gate crosscoupled charge-pump topology with TFETs powered by a thermogenerator presents a peak power conversion efficiency (PCE) of 74% for a temperature variation of 1 K (Vin=80 mV). In another work, the authors have shown similar PCE improvements in RF passive rectifiers based on TFETs for input power levels below -30 dBm (typical far-field ambient RF-power) [11]. These results are highly motivating for several applications where the power requirements of external batteries are still mandatory to ensure a proper circuit operation.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…In [10] we have shown that a gate crosscoupled charge-pump topology with TFETs powered by a thermogenerator presents a peak power conversion efficiency (PCE) of 74% for a temperature variation of 1 K (Vin=80 mV). In another work, the authors have shown similar PCE improvements in RF passive rectifiers based on TFETs for input power levels below -30 dBm (typical far-field ambient RF-power) [11]. These results are highly motivating for several applications where the power requirements of external batteries are still mandatory to ensure a proper circuit operation.…”
Section: Introductionmentioning
confidence: 74%
“…This characteristic can result in switching nodes with transient "spikes", with voltage values above the power supply voltage and below ground. For TFET-based charge-pumps and rectifier, this behavior can induce an increased switching power as referred in [11].…”
Section: Tunnel Fet Intrinsic Capacitancementioning
confidence: 99%
See 2 more Smart Citations
“…The received RF signals cannot be converted into DC (i.e., energy transfer) if their power level is lower than the power sensitivity of an RF-DC circuit [19]. Thus, actually received energy would be much lower than the theoretically predicted amount, leading to a falsely higher data rate.…”
mentioning
confidence: 99%